Rosmarinic acid ameliorates hyperglycemia and insulin sensitivity in diabetic rats, potentially by modulating the expression of PEPCK and GLUT4 - Runtuwene J; Cheng KC; Asakawa A; Amitani H; Amitani M; Morinaga A; Takimoto Y; Kairupan BHR; Inui A (Dove Medical Press, 2016)
Joshua Runtuwene,1,2 Kai-Chun Cheng,1 Akihiro Asakawa,1 Haruka Amitani,1 Marie Amitani,1 Akinori Morinaga,1 Yoshiyuki Takimoto,3 Bernabas Harold Ralph Kairupan,2 Akio Inui1 1Department of Psychosomatic Internal Medicine, Kagoshima University Graduate School of Medical and Dental Sciences, Kagoshima, Japan; 2Faculty of Medicine, Sam Ratulangi University, Manado, Indonesia; 3Department of Biomedical Ethics, Graduate School of Medicine, The University of Tokyo, Tokyo, Japan Background: Rosmarinic acid (RA) is a natural substance that may be useful for treating diabetes mellitus. The present study investigated the effects of RA on glucose homeostasis and insulin regulation in rats with streptozocin (STZ)-induced type 1 diabetes or high-fat diet (HFD)-induced type 2 diabetes.Methods: Glucose homeostasis was determined using oral glucose tolerance tests and postprandial glucose tests, and insulin activity was evaluated using insulin tolerance tests and the homeostatic model assessment for insulin resistance. Additionally, the protein expression levels of PEPCK and GLUT4 were determined using Western blot analysis.Results: RA administration exerted a marked hypoglycemic effect on STZ-induced diabetic rats and enhanced glucose utilization and insulin sensitivity in HFD-fed diabetic rats. These effects of RA were dose-dependent. Meanwhile, RA administration reversed the STZ- and HFD-induced increase in PEPCK expression in the liver and the STZ- and HFD-induced decrease in GLUT4 expression in skeletal muscle.Conclusion: RA reduces hyperglycemia and ameliorates insulin sensitivity by decreasing PEPCK expression and increasing GLUT4 expression. Keywords: diabetes mellitus, STZ, HFD, HOMA-IR, PEPCK, GLUT4